Chronic illness and functional limitation in Ontario children: findings of the Ontario Child Health Study. - Cadman, D (1986)
The Ontario Child Health Study (OCHS) was based on interviews of 1869 Ontario families who were selected by means of a stratified, multistaged sampling method from the 1981 census of Canada. Its primary purpose was to determine the prevalence and distribution of mental health problems in Ontario children aged 4 to 16 years and their families, but it also allowed an estimate of other significant medical conditions and provided an overview of these children's use of health care, education and social services. Our results are based on questionnaire responses concerning 3294 children. Limitation of function without a chronic illness or medical condition was reported in 1.9%, the converse in 14.0%, and a chronic illness or medical condition with limitation of function in 3.7%. When the three groups are considered together, 19.6% of Ontario children had a chronic health problem. Children of lower socioeconomic status were much more likely to have chronic health problems. Overall, children with chronic health problems were more likely to use physician, special education, social and mental health services. These findings have implications for those who provide services for children, plan community programs or train professionals in caring for children.